Analiza stanja lišajev v popisu stanja gozdov v letu 2007 - Batič, Franc (Gozdarski vestnik, 2011)
Epiphytic lichen cover of crustose, foliose and fructicose lichens has been assessed within the standardized grid laid on trunks of the chosen, comparable tree species on the plots of forest inventory in 2007. Median cover of crustose, foliose and fructicose epiphytic lichens are presented in grouped analyses for all trees. The cover of crustose lichens is presented additionally for common beech and the cover of foliose lichens for Norway spruce. Generally, the epiphytic lichen cover is poor, the richest is the cover of crustose and the poorest is the cover offructicose lichens. Plots with major lichen cover are situated in remote areas with cleaner air while plots with minor epiphytic lichen cover are situated in areas affected by local sources of air pollution, some also in areas where transboundary input of air pollutants takes place. Epiphytic lichen cover increases slightly with the age of the forests stands, other stand and site parameters have no major influence. In spite of the reduction of air pollution by sulphur compounds in the last two decades in Slovenia the epiphytic lichens cover in forests remains poor. The most probable reason is the persisting air pollution by nitrogen compounds from traffic, thermal power plants, industry, agriculture and other sources. The worsened state of the epiphytic lichen cover is, to a certain extent, also the consequence of themonitoring method in which the epiphytic lichens are assessed only in the lower part of tree trunks where light conditions are not always suitablefor their growth.
Keywords: gozdovi; popis stanja; gozdna inventura; epifitski lišaji; bioindikatorji; onesnaženje zraka; Slovenia; Slovenija